Interactions between the oyster larvae pathogen Vibrio ostreicida and the bivalve hosts Mytilus galloprovincialis and Magallana gigas - Leonessi, Martina; Auguste, Manon; Lopez, Jose R.; Balbi, Teresa; Ciacci, Caterina; Oliveri, Caterina; Vezzulli, Luigi; Furones, Dolors; Canesi, Laura (Frontiers in Immunology, 2025)
IntroductionMarine bivalves are continuously exposed to a variety of environmental stressors, including different Vibrio species potentially involved in disease outbreaks that have severely impacted farmed populations over the past two decades. Vibrio ostreicida was firstly identified as a lethal pathogen for oyster larvae (Ostrea edulis), but its interactions with the immune system of the bivalve host are largely unexplored.MethodsIn this study, we investigated the pathogenic potential of a V. ostreicida strain r172, isolated from a 2022 mortality event in adult Mytilus galloprovincialis in the Ebro Delta (Spain), focusing on mussel early larval development and hemolymph immune responses in in vitro short-term exposure experiments. Immune responses were compared with those of the oyster Magallana gigas.ResultsBoth live and heat-killed V. ostreicida significantly impaired normal larval development with a dose-concentration effect (EC50 ≈ 103 - 104 CFU/mL), with live bacteria inducing shell malformations and heat-killed Vibrio causing developmental arrest. In the hemocytes of adult mussels, exposure to heat-killed V. ostreicida led to dose-dependent lysosomal destabilization, reduced phagocytic activity, and increased intracellular ROS production. Similar lysosomal destabilization was observed with live V. ostreicida, which also stimulated extracellular ROS and nitric oxide release, but only in the presence of hemolymph serum (HS). Mussel HS displayed a strong bactericidal activity towards V. ostreicida, highlighting a key role for soluble immune effectors. In oyster hemocytes, V. ostreicida induced similar lysosomal stress; however, neither hemocytes nor serum showed any bactericidal activity towards this strain.DiscussionThis data represents the first attempt to elucidate the mechanisms underlying the interactions of an environmental strain of V. ostreicida with marine bivalves. The species-specific differences observed in immune responses highlight the complexity of host-pathogen interactions in these organisms and emphasize the need for further investigation into immune responses of different aquacultured species.